America on trial : inside the legal battles that transformed our nation - Dershowitz, Alan M. (New York : Warner Books, 2004)
The renowned attorney examines several of the most controversial and sensational court trials of the past thirty years, offering insight into how they have shaped present-day politics and society.
Introduction ; Prologue: the foundations of American law -- Pt. I. Colonial America. The Salem witchcraft trials ; The trial of John Peter Zenger ; The slave revolt trial ; The Boston Massacre trials -- Pt. II. Early history of the US. The trials of aliens and seditioners ; The treason trial of Aaron Burr -- Pt. III. From Jacksonian democracy to the pre-Civil War period. The Boorn-Colvin murder mystery ; The Richard Lawrence case ; The Harvard Medical School murder -- Pt. IV. The prelude to the Civil War. The Dred Scott case ; The John Brown trial -- Pt. V. The Civil War. The Savannah case ; The trial of Captain Henry Wirz ; The trial of the Lincoln assassins -- Pt. VI. The post-Civil War period. The trial of Andrew Johnson ; The trial of Susan B. Anthony ; The trial of Mary Todd Lincoln ; The trial of the assassin Guiteau ; The trial of Lizzie Borden -- Pt. VII. Early 20th century. The trial of Stanford White's killer ; The great labor union trials ; The trial of Leo Frank ; The Abrams case ; The Shoeless Joe Jackson case -- Pt. VIII. The Roaring 20's" and the Depression 30's. The trial of Sacco and Vanzetti ; The trial of Leopold and Loeb ; The Scopes trial ; The court-martial of Billy Mitchell ; The Lindbergh kidnapping trial ; The Scottsboro trials -- Pt. IX. World War II. The Nuremberg trials ; The Ezra Pound case -- Pt. X. The Cold War and McCarthyism. The Alger Hiss case ; The trial of the Rosenbergs ; The Remington case -- Pt. XI. The civil rights movement. Brown [v. Board of Education of Topeka, Kansas] case ; The prosecution of Martin Luther King Jr. ; The case of Clarence Earl Gideon ; The trial of Jack Ruby -- Pt. XII. The Vietnam War era and its aftermath. The trial of Dr. Spock ; The trial of the Chicago Seven ; The court-martial of Lieutenant William L. Calley Jr. ; The Pentagon papers case ; Roe v. Wade ; The American Indian movement trials; The Bakke case ; The trial of Richard Herrin ; The trial of Jeffrey MacDonald -- Pt. XIII. 1980's and 1990's. The trial of Jean Harris for the Scarsdale diet doctor murder ; The attempted assassination of President Reagan by John Hinkley Jr. ; The trials and appeal of Claus von Bulow ; The John DeLorean trial ; Flynt v. Falwell ; The Bernhard Goetz case ; The McMartin case ; The Central Park jogger case ; The trial of Mike Tyson ; The two trials for the beating of Rodney King ; The O.J. Simpson trial ; The Clinton impeachment trial -- Pt. XIV. The new millennium and the future. The Bush v. Gore ; The Texas sodomy trial and appeal ; The cases of the terrorist detainees--in Guantanamo, on the U.S. mainland, and in unknown places around the world.
Includes bibliographical references and index.
Keywords: Trials -- United States; Law -- United States -- History